Analisis Perbandingan Teknik Pemilihan Cluster Head Pada Wireless Sensor Network Berbasis Clustering Menggunakan Algoritma Routing Protocol LEACH dan G-LEACH - Kristoforus Fallo; Budiman Baso (Journal of Information and Technology, 2023)
Wireless Sensor Network (WSN) is a series of wireless networks consisting of several nodes in a limited area. Low Energy Adaptive Clustering Hierarchy (LEACH) and Grid-Based Low Energy Adaptive Clustering Hierarchy (G-LEACH) methods are clustering methods used to collet data by clustering nodes in the WSN area. The clustering process for both methods is the same, namely by select node as the Cluster head (CH) whose job is to collet data from other nodes to the sink. The selection of CH is carried out in each round by taking into account the probability formula used and the largest the remaining energy at that node. This study aims to determine the quality comparison of CH selection techniques in clustering-based routing protocol on WSN. The result of the study show that the G-LEACH routing protocol has good quality CH selection techniques and a long network lifetime compared to LEACH but requires a long time to reach the CH selection process